2022
DOI: 10.1108/bfj-03-2022-0299
|View full text |Cite
|
Sign up to set email alerts
|

Let's talk about straw: the effect of information provision on consumers' attitudes towards pig husbandry systems

Abstract: PurposeThe type of flooring in stalls is an important factor that shapes consumers' overall perception of animal husbandry. Although slatted and straw floors have benefits and drawbacks, consumers strongly prefer slatted over straw floors in pig husbandry. The present study investigates whether information provision can depolarise consumers' implicit and explicit attitudes towards both floor types to enable a more realistic evaluation of pig husbandry systems. Furthermore, this study examines the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…It can be assumed that information provision changes both implicit and explicit attitudes, but Gawronski and Bodenhausen [ 3 ] illustrated that this is not necessarily always the case. Empirical research has also shown that the mediating role of implicit and explicit attitudes requires further exploration [ 4 ]. Therefore, this dataset enables further investigation on this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that information provision changes both implicit and explicit attitudes, but Gawronski and Bodenhausen [ 3 ] illustrated that this is not necessarily always the case. Empirical research has also shown that the mediating role of implicit and explicit attitudes requires further exploration [ 4 ]. Therefore, this dataset enables further investigation on this relationship.…”
Section: Introductionmentioning
confidence: 99%